2020
DOI: 10.3389/fimmu.2020.01701
|View full text |Cite
|
Sign up to set email alerts
|

Bovine IgG Prevents Experimental Infection With RSV and Facilitates Human T Cell Responses to RSV

Abstract: Respiratory syncytial virus (RSV) infections represent a major burden of disease in infants and are the second most prevalent cause of death worldwide. Human milk immunoglobulins provide protection against RSV. However, many infants depend on processed bovine milk-based nutrition, which lacks intact immunoglobulins. We investigated the potential of bovine antibodies to neutralize human RSV and facilitate-cell immune activation. We show cow's milk IgG (bIgG) and Intravenous Immunoglobulin (IVIG) have a similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Examples include findings that BC supplementation reduced the number of flu-like episodes [ 141 ]. BC supplementation has also been reported to be beneficial in reducing the number of upper respiratory tract infections (URTIs) and diarrhoeal episodes in children [ 142 , 143 ], and BC IgG has been shown to bind and neutralise human respiratory syncytial virus [ 144 ]. Similarly, athletes undergoing training are known to have increased risk of URTI symptoms, and metanalyses of published trials reported a significant positive effect of BC supplementation [ 145 ].…”
Section: Bc Use In Human and Veterinary Healthmentioning
confidence: 99%
“…Examples include findings that BC supplementation reduced the number of flu-like episodes [ 141 ]. BC supplementation has also been reported to be beneficial in reducing the number of upper respiratory tract infections (URTIs) and diarrhoeal episodes in children [ 142 , 143 ], and BC IgG has been shown to bind and neutralise human respiratory syncytial virus [ 144 ]. Similarly, athletes undergoing training are known to have increased risk of URTI symptoms, and metanalyses of published trials reported a significant positive effect of BC supplementation [ 145 ].…”
Section: Bc Use In Human and Veterinary Healthmentioning
confidence: 99%
“…Human respiratory syncytial virus (RSV) is a common, contagious virus that causes respiratory infections, namely bronchiolitis, common cold, and serious illness for infants and elderly persons. To study the preventive action of isolated IgG from bovine colostrum in response to RSV, an animal trial was carried out by Nederend et al [ 100 ]. BC was collected within 5 days after parturition, and IgG was isolated from whey by using affinity purification and evaluated for a binding property with culture HEp-2 cells infected with two strains of RSV in a mouse model (in vitro).…”
Section: Current Evidence Of Therapeutic Use Of Bcmentioning
confidence: 99%
“…bIgG promotes adaptive antiviral T cell responses and protects against RSV infection in vitro and in vivo. Therefore, purified bIgG can be added to infant formulas to pass some of the beneficial effects of raw bovine milk to microbiologically stable infant formulas (Nederend et al 2020), which not undergo heat treatment to avoid reducing the protective effect of bovine milk (Mainer et al 1997;Loss et al 2015). Bovine lactoferrin (BL), protein found in cow milk, indirectly reduces human norovirus infection via inducing the innate interferon responses (Oda et al 2021) and has a therapeutic potential against SARS-CoV-2 (Batista da Silva Galdino et al 2021).…”
Section: Bovine-derived Productsmentioning
confidence: 99%